The new scramble for Africa in a post-colonial era and the challenges of inclusive development: a semi-systematic literature review - Victor H. Mlambo; Mfundo Mandla Masuku; Zinhle Mthembu (Development Studies Research)
The African populace met the end of colonialism in Africa with jubilation. There was hope that its demise would lead to socioeconomic emancipation after decades of segregation, discrimination and denial of local values and traditions. Nevertheless, what emerged has been the total opposite: corruption, never-ending conflict, the rise of violent non-state actors, elitism, poverty, and inequality. This gave rise to a new scramble for Africa, as major powers compete for influence on the continent. To investigate the difficulties of consolidating inclusive development in post-colonial Africa, this paper employed a semi-systematic research approach. The authors searched for peer-reviewed, English-language literature published from 1998 to 2023 through five online databases (Google Scholar, Sabinet, SAGE journals, Social Science Citation Index, Web of Science and EBSCOhost). The new scramble for Africa appeared to have presented so far both opportunities and risks. As great powers compete for influence and deeper relations, Africa is caught in the middle. It remains to be seen whether this scramble will be different from the previous colonization and whether it will foster the consolidation of inclusive development in Africa.